Analisis Faktor-Faktor yang Menentukan Kepuasan Kerja dan Loyalitas Karyawan (Studi Kasus di Perusahaan Kopi PT Golden Kirrin Internasional, Kabupaten Badung) - SITINJAK, DESMAN ARIANTO; SURYAWARDANI, GUSTI AYU OKA; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.3, Juli 2017, 2017)
The Analysis the Factors that Determinate Employee’s Job Satisfaction and Loyalty (The Case at Company’s Coffee by Golden Kirrin International, Badung Regency) This research aims to analyze the factors that determine the job satisfaction and employee loyalty in PT Golden Kirrin International. The research was conducted in the agro-tourism company PT Golden Kirrin International, Badung Regency, Bali Province, with 109 respondents interviewed. The data were analyzed by exploratory factor analysis using SPSS. The results showed that job satisfaction and loyalty of employees of PT Golden Kirrin International supported by three factors, namely: social factor with the indicators are: motivation, the attitude of the leadership relationship led to the employee, employee relations with employees, work space, and punishment. Salary/wage factor with the indicators are: salaries/wages, allowance (Tunjangan Hari Raya), bonuses, job description, holidays, and reward. Work assurance factor with the indicators are: job security and safety assurance. The result of the assessment employee loyalty was analyzed from three indicators showed an excellent result, employees are very satisfied with company’s and employee’s performance and employees are very loyal to the company PT Golden Kirrin Internasional. The advice that can be given on the result of this study to PT Golden Kirrin International is that the leadership of PT Golden Kirrin International must maintain the level of satisfaction and loyalty of its employees, especially in the social and salary/wage factors. Because these factors are very significant impact on the achievements that have been set by the company. As for, the work assurance factor corporate leaders still have to pay attention, because this factor supports the creation of the welfare of the employees working.